Khảo sát phản ứng C-axetyl hóa một số aryl metyl ete trong điều kiện hóa học xanh - Phương, Trần Hoàng; Thạch, Lê Ngọc (Vietnam Journal of Chemistry, 2014)
Alkyl aryl ketone is an important intermediate in the synthesis of biologically active molecules. It is usually synthesized by Friedel-Crafts acylation of aromatic compound in the presence of excess Lewis acid, AlCl3. In this study, copper triflate Cu(OTf)2was used as a new generation Lewis acid catalyst in Friedel-Crafts acylation. The reaction was taken place under microwave irradiation on anisole and veratrole. Copper triflate is safe-to-handle, recoverable and reusable